Betty Catroux, Yves Saint Laurent - féminin singulier = Betty Catroux, Yves Saint Laurent - feminine singular - Bailleux, Nathalie (Gallimard, 2020)
"Betty Catroux, Yves Saint Laurent's female double, embodies in the couturier's eyes the androgynous woman and a certain feminine ideal. She personified, better than anyone else, the fascinating enigma of Saint Laurent and his long silhouettes, celebrated around the world and immune to passing trends. One of his closest friends, she was the only model able to keep prototypes of each collection. A collection she just donated to the Yves Saint Laurent Museum 1,200 pieces (clothing and accessories). This book presents photographs from the museum's collections and Betty Catroux's personal collection, selected by Anthony Vaccarello." -- Website
Diese Publikation erscheint anlässlich der gleichnamigen Ausstellung im Musée Yves Saint Laurent Paris 03.03.2020-11.10.2020
Keywords: Saint Laurent, Yves -- 1936-2008; Catroux, Betty -- 1945-; Catroux, Betty; Saint Laurent, Yves; Musée Yves Saint Laurent (Paris, France) / Exhibitions; Fashion designers / France / Portraits; Models (Persons) / France / Portraits; Ausstellungskatalog -- Musée Yves Saint Laurent -- 03.03.2020-11.10.2020 -- Paris; Bildband